Determinants of Economic Growth in ASEAN-5: A Sharia Economics Analytical Perspective - Ahsanal Huda; Anton Bawono; Muhammad Iqbal; Wan Ruslan Abdul Ghani; Khavid Normasyhuri (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
Economic growth in ASEAN countries faces persistent challenges from macroeconomic instability and structural constraints. This study examines labor, inflation, exchange rates, and foreign direct investment (FDI)as determinants of economic growth in the ASEAN-5, namely Indonesia, Vietnam, Malaysia, the Philippines, and Thailand. Employing a quantitative associative method, the research uses panel data from the World Bank period 2004 until 2023 with a total of 100 observations and applies a Fixed Effect Model using Eviews 12. The results indicate that inflation, exchange rates, and FDI significantly determine economic growth, whereas labor does not. The key empirical contribution is to provide robust, country-specific evidence that can guide policymakers in prioritizing macroeconomic stability and investment climate reforms over labor quantity expansion to sustain regional growth. From a Sharia economics perspective, growth must uphold justice, balance, and holistic welfare.